2016
DOI: 10.1080/17429145.2016.1163423
|View full text |Cite
|
Sign up to set email alerts
|

The heterologous expression of aGlycine maxhomolog of NONEXPRESSOR OF PR1 (NPR1) and α-hydroxynitrile glucosidase suppresses parasitism by the root pathogenMeloidogyne incognitainGossypium hirsutum

Abstract: Experiments in Glycine max (soybean) identified the expression of the salicylic acid signaling and defense gene NONEXPRESSOR OF PR1 (NPR1) in root cells (i.e., syncytium) parasitized by the plant parasitic nematode Heterodera glycines undergoing the process of resistance. Gm-NPR1-2 overexpression in G. max effectively suppresses parasitism by H. glycines. The heterologous expression of Gm-NPR1-2 in Gossypium hirsutum impairs the ability of the parasitic nematode Meloidogyne incognita to form root galls, egg sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 79 publications
1
20
0
Order By: Relevance
“…These findings along with the previous work (Pant et al 2016) indicate that α-hydroxynitrile glucoside exists in G. hirsutum. There are possibilities that cyanide detoxification route/pathway (Gleadow and Moller 2014;Machingura et al 2016;Ting and Zschoche 1970;Zagrobelny et al 2004;Miller and Conn 1980;Sun et al 2018;Nielsen et al 2016;Pičmanová et al 2015) is more active in cotton.…”
Section: Lessons Learned From Transient Expressionsupporting
confidence: 87%
“…These findings along with the previous work (Pant et al 2016) indicate that α-hydroxynitrile glucoside exists in G. hirsutum. There are possibilities that cyanide detoxification route/pathway (Gleadow and Moller 2014;Machingura et al 2016;Ting and Zschoche 1970;Zagrobelny et al 2004;Miller and Conn 1980;Sun et al 2018;Nielsen et al 2016;Pičmanová et al 2015) is more active in cotton.…”
Section: Lessons Learned From Transient Expressionsupporting
confidence: 87%
“…Cherif et al [70] showed that an increase in beta-glucosidase activity in cucumber roots was associated with silicon-induced resistance to Pythium spp. Another study demonstrated that a soybean beta-glycosidase related to the Lotus japonicus defense gene, a-hydroxynitrile glucosidase, suppresses the parasitic activities of the nematode Meloidogyne incognita [71]. Furthermore, Miche et al [72] identified a putative endo-1,3-beta-D-glucosidase as part of the jasmonate-induced defense-responsive proteins in the roots of rice plants upon exposure to the endophyte Azoarcus sp.…”
Section: Resultsmentioning
confidence: 99%
“…The heterologous expression of genes identified in one plant (G. max) in another recipient plant (G. hirsutum) has been demonstrated to be an effective way to understand the genetics of defense in various plant-parasitic nematode pathosystems by generating resistance outcomes under conditions where they may not normally exist. For example, a number of G. max genes and various bacterial effectors have been tested in the G. hirsutum-M. incognita pathosystem showing that they function to impair parasitism [37][38][39][40]. Pant et al (2016) showed that the G. max homolog of the A. thaliana transcription factor NONEXPRESSOR OF PR1 (NPR1) functions effectively to suppress M. incognita parasitism in G. hirsutum [37,41].…”
Section: Plos Onementioning
confidence: 99%
“…For example, a number of G. max genes and various bacterial effectors have been tested in the G. hirsutum-M. incognita pathosystem showing that they function to impair parasitism [37][38][39][40]. Pant et al (2016) showed that the G. max homolog of the A. thaliana transcription factor NONEXPRESSOR OF PR1 (NPR1) functions effectively to suppress M. incognita parasitism in G. hirsutum [37,41]. Furthermore, the bacterial effector harpin, first identified from the fire blight pathogen Erwinia amylovora, was capable of activating the expression of the coiled-coil nucleotide binding leucine rich repeat (CC-NB-LRR) NON-RACE SPECIFIC DISEASE RESISTANCE 1 (NDR1) in G. max [39,[42][43][44].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation